THE EFFECT OF BOARD CHARACTERISTICS ON TAX AVOIDANCE WITHSUSTAINABILITY PERFORMANCE AS A MEDIATING VARIABLE - Melissa Melissa; Iskandar Itan (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
This study aimed to examine the correlation between the board of directors’ characteristics and tax avoidance and the mediating role of sustainability performance on the correlation between the board of directors’ characteristics and corporate tax avoidance. This study employed a purposive sampling method and found 33 companies listed on the Indonesia Stock Exchange (IDX) that met the sample criteria for the 2016-2020 period. The results show that all independent variables including gender diversity, independent commissioners, and the size of the board of directors do not have a strong effect on the level of tax avoidance in Indonesia. The findings also show that sustainability performance does not mediate the relation of board characteristics and tax avoidance in Indonesia.